Shoot multiplication of Pogostemon cablin var. Sidikalang and patchouli oil profile - POPY HARTATIE HARDJO; DANNY PUTRA SENTOSA SUSANTO; WINA DIAN SAVITRI; MARIA GORETTI MARIANTI PURWANTO (Nusantara Bioscience, 2019)
Abstract. Hardjo PH, Susanto DPS, Savitri WD, Purwanto MGM. 2019. Shoot multiplication of Pogostemon cablin var. Sidikalang and patchouli oil profile. Nusantara Bioscience 11: 123-127. Pogostemon cablin Benth. is a plant producing patchouli oil, which mostly consists of patchouli alcohol compound. Patchouli oil has great potentials in the world market because of its stability and high price. In this study, in vitro multiplication of Sidikalang variety of Acehnese patchouli shoots was done on solid and liquid Murashige & Skoog (MS) medium. This study aimed to determine the effect of cytokinins in various combinations of shoot multiplication and to compare the patchouli oil yield of in vitro and ex vitro culture. In vitro multiplication of Acehnese patchouli shoots by using solid MS medium with addition of 0.2 ppm benzyl aminopurine (BAP) and 0.2 ppm Kinetin resulted in shoot explants with an average growth index of 82.198 ± 0.690. Patchouli oil extraction was done on 7 weeks old in vitro shoot explants cultured on solid MS medium + 0.2 ppm BAP + 0.2 ppm Kinetin using water distillation method. In vitro shoots yielded 2.5% patchouli oil and contained ± 35% patchouli alcohol compound, whereas ex vitro shoots produced 4% patchouli oil and contained ± 25% patchouli alcohol compound. The qualitative analysis by using thin layer chromatography (TLC) showed that there were similarities in the number of spot and Rf value for each spot of ex vitro and in vitro patchouli oil.